“Agora é a vez do pixo” : cenas de dissenso e subjetivação política nas relações entre pixação e arte. - Ana Karina de Carvalho Oliveira (2015)
This study seeks to analyze the opening, by the pixadores of São Paulo, of spaces of relation with the art world, producing scenes of dissensus and processes of political subjectification that keeps a potential for the reconfigurations of the names, places and functions that are commonly given to them. The work was developed, among other authors, from the political though of Jacques Rancière, for whom the politics is the questioning about the places given by the hierarchy of a social order that imposes a mode of partition of the sensible: the police order. The analysis is made from six events occurred between 2008 and 2012 – three invasions and three invitations – that interlaced in a tense and conflicted way the universes of pixação and art, mixing up the relations and the expectations given to each other until so. From that context and grounding, the aim of the research is to analyze the creation of scenes of dissensus and the processes of political subjectification built from the disidentification of the pixadores with the names assigned to them by the institutional, juridical and artistic levels, evidencing a polemical and conflictual insertion in the field of art. Therefore, the construction of the analysis is given in order to reconstitute the scenes of each event from the elements that configure a scene of dissensus, emphasizing the actors involved, their designation, the distribution of places, the ordinations of functions and relations, the presence of the pixação, the acting of the pixadores and the consequences. From then, each event is analyzed in three categories: the tensions between consensus and dissensus; the forms of entry and visibility; and the political subjectification. The modes as the pixadores name and enact a wrong, disidentify themselves from the names and places that are given to them e demonstrate by argument their experience and situation, beyond the ways in which they contest or negotiate with the established scenes. At the end, the events are analyzed in their intersections and entanglements as a complex process, in order to perceive, from the complete trajectory, if the forms of visibility and treatment of the pixação are transformed. The results indicate that, although there aspects that demonstrate some changes in the forms of relation,seizure and presentation of the pixação, they are very specific of that context of approach with the field of art, not extending to other spheres, specially the street, the common and everyday environment of the pixação.